2022
DOI: 10.1038/s41598-022-14437-x
|View full text |Cite
|
Sign up to set email alerts
|

Probing Notch1-Dll4 signaling in regulating osteogenic differentiation of human mesenchymal stem cells using single cell nanobiosensor

Abstract: Human mesenchymal stem cells (hMSCs) have great potential in cell-based therapies for tissue engineering and regenerative medicine due to their self-renewal and multipotent properties. Recent studies indicate that Notch1-Dll4 signaling is an important pathway in regulating osteogenic differentiation of hMSCs. However, the fundamental mechanisms that govern osteogenic differentiation are poorly understood due to a lack of effective tools to detect gene expression at single cell level. Here, we established a dou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…The previous study has shown that Notch signaling is involved during hMSCs osteogenic differentiation, disruption of Notch signaling mediated ALP activity, and osteogenic differentiation efficiency. Our group also recently showed that Dll4 mRNA is a molecular biomarker of osteogenic differentiated hMSCs ( Zhao et al, 2022 ). Inhibition of Notch signaling reduces osteogenic differentiation with decreased ALP enzyme activity.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…The previous study has shown that Notch signaling is involved during hMSCs osteogenic differentiation, disruption of Notch signaling mediated ALP activity, and osteogenic differentiation efficiency. Our group also recently showed that Dll4 mRNA is a molecular biomarker of osteogenic differentiated hMSCs ( Zhao et al, 2022 ). Inhibition of Notch signaling reduces osteogenic differentiation with decreased ALP enzyme activity.…”
Section: Resultsmentioning
confidence: 84%
“…A fluorophore (6-FAM (fluorescein)) was labeled at the 5′ end of the LNA detecting probe for mRNA detection. Design, characterization, and optimization of LNA/DNA nanobiosensor have been reported previously ( Wang et al, 2015 ; Zheng et al, 2017 ; Wang et al, 2018a ; Zhao et al, 2022 ). Briefly, the LNA probe will bind to the quencher spontaneously to form a LNA - quencher complex.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations